Inventing the future : postcapitalism and a world without work - Srnicek, Nick; Williams, Alex, 1981- (Tantor Media, Inc., 2023)
This major new manifesto offers a "clear and compelling vision of a postcapitalist society" and shows how left-wing politics can be rebuilt for the twenty-first century (Mark Fisher, author of Capitalist Realism Neoliberalism isn't working. Austerity is forcing millions into poverty and many more into precarious work, while the left remains trapped in stagnant political practices that offer no respite. Inventing the Future is a bold new manifesto for life after capitalism. Against the confused understanding of our high-tech world by both the right and the left, this book claims that the emancipatory and future-oriented possibilities of our society can be reclaimed. Instead of running from a complex future, Nick Srnicek and Alex Williams demand a postcapitalist economy capable of advancing standards, liberating humanity from work and developing technologies that expand our freedoms. This new edition includes a new chapter where they respond to their various critics